The role of proton dynamics in the development and maintenance of multidrug resistance in cancer - Daniel, Chloë; Bell, Charlotte; Burton, Christopher; Harguindey, Salvador; Reshkinc, Stephan J.; Rauch, Cyril (Elsevier, 2013)
With a projected 382.4 per 100,000 people expected to suffer from some form of malignant neoplasm in 2015, improving treatment is an essential focus of cancer research today. Multi-drug resistance (MDR) is the leading cause of chemotherapeutic failure in the treatment of cancer, the term denoting a characteristic of the disease-causing agent to avoid damage by drugs designed to bring about their destruction. MDR is also characterised by a reversal of the pH gradient across cell membranes leading to an acidification of the outer milieu and an alkalinisation of the cytosol that is maintained by the proton pump vacuolar-type ATPase (V-ATPase) and the proton transporters: Na+/H+ exchanger (NHE1), Monocarboxylate Transporters (MCTs), Carbonic anhydrases (CAs) (mainly CA-IX), adenosinetriphosphate synthase, Na+/HCO3− co-transporter and the Cl−/HCO3−exchanger. This review aims to give an introduction to MDR. It will begin with an explanation for what MDR actually is and go on to look at the proposed mechanisms by which a state of drug resistance is achieved. The role of proton-pumps in creating an acidic extracellular pH and alkaline cytosol, as well as key biomechanical processes within the cell membrane itself, will be used to explain how drug resistance can be sustained.